Optimalisasi Kapasitas Dan Peningkatan Efisiensi Biaya Pengelolaan Kelas Karyawan - Nurhayati, Immas; Suharti, Titing (inovator, 2018)
This research would like to analysis optimizing employee class management both in capacity and cost efficiency. Capacity optimization is to determine the minimum number of students that can cover all of their class costs. The research method uses break even point analysis. The results of the study showed that the optimal number of class capacity was 21 (twenty one) students. Taking into account efficiency and fairness for all, excess teaching fees per SKS for employee classes vary from Rp. 12,500 to Rp. 50,000 with the presence of Rp. 50,000.